A new Zn(ii) complex-composite material: piezo-enhanced photomineralization of organic pollutants and wastewater from the lubricant industry. Issue 10 (26th August 2021) - D., Venkateshwar Rao; Subburu, Mahesh; Gade, Ramesh; Basude, Manohar; Chetti, Prabhakar; Simhachalam, Narendra Babu; Nagababu, Penumaka; Bhongiri, Yadagiri; Pola, Someshwar
Abstract : A ZnO–[Zn(CPAMN)] complex-composite acts as a piezo-photocatalyst for the degradation of dyes pollutants and industry wastewater under ultrasonication and visible light irradiation due to the low rate of electron–hole pair recombination. Abstract : In the current work, a ZnO–[Zn(CPAMN)] complex-composite material was used as a piezo-photocatalyst for the mineralization of organic dye pollutants and industrial wastewater. The ZnO–[Zn(CPAMN)] complex-composite material showed higher piezo-photocatalytic activity than a simple complex or ZnO. In contrast, the lower bandgap (2.22 eV) makes it easy for the complex-composite to excite photo-generated species under visible light. Instead, the piezoelectric field initiated from the twisting distortion of [ZnO–Zn(CPAMN)] efficiently enhanced the charge-carrier separation and repositioning. Ultrasonic vibration and visible light radiation applied simultaneously to the complex-composite catalyst mineralized 98% of methyl red (MR) and rhodamine B (RhB) dye solutions during the piezo-photocatalytic process within 60 and 80 min, respectively. The reaction MR constant k of the piezo-photocatalysis process was 50 and 20 times higher than those of sole piezocatalysis and photocatalysis, respectively. The pollutants in industrial wastewater samples were effectively mineralized by over 95% compared to the use of simple piezocatalysis and photocatalysis. Compared to precursor materials such as [Zn(CPAMN)] and ZnO, the significant catalytic activity of the ZnO–[Zn(CPAMN)] complex-composite arose because of heterojunction superiority due to the low rate of recombination of active species and the high surface area.